Clinical pharmacy undergraduate education in China: a comparative analysis based on ten universities’ training programs - Jiakai Li; Chenlin Xiao; Jingjing Hou; Yichang Zhao; Hui Gong; Bikui Zhang; Miao Yan (BMC Medical Education, 2023)
Abstract Background In recent years, the scale of personnel training for clinical pharmacy professionals in China has expanded increasingly, however, the shortage of clinical pharmacists is still prominent. In 2018, the Ministry of Education of China released national standards for the teaching quality of undergraduate majors at regular colleges and universities, which has developed a core policy for undergraduate clinical pharmacy training. To explore the training methods for clinical pharmacy professionals in China and to promote the healthy and sustainable development of the clinical pharmacy education system. This study comparatively analyzed the training programs for clinical pharmacy undergraduates in China’s ten universities, discussed training programs suitable for clinical pharmacy professionals in China. Methods The clinical pharmacy education programs in these ten universities were obtained through official school websites or by interviewing relevant people, and then compared and analyzed. Results The school with the largest number of courses and the most class hours in general courses is University A1 (34 courses, 1316 class hours), and the school with the most credits is University B1 (75.5 credits). The schools with the largest number of courses and the most class hours in the basic courses are University A1 (50 courses, 1997 class hours), and the schools with the most credits are University B3 and University B1 (105.5 credits). The schools with the largest number of courses in the core courses are University C1 (23 courses), and the school with the most credits and class hours is University B2 (51 credits, 914 class hours). The school with the most class hours in practical teaching is University B6 (1406 class hours), and the schools with the longest internship time are University A1 and University B6 (52 weeks). Conclusions There was substantial variation in programs. There remains a gap between the existing educational model and clinical training in pharmacy in China and developed countries. China should explore the most appropriate method for undergraduate education in clinical pharmacy based on studying foreign excellent educational models and the experience of China.